Assessing sales downtrend among small retailers in Iloilo City - Bayona, Suzy Lyn A.; Tan, Lelanie S. (1995.)
Executive Summary-retailing is an important part of Philippine society and Iloilo City in particular. Retailing is affected by the factors in the environment such as demographics, political, lifestyle trends, changing role of women, consumerism, and technological developments. The observed downtrend in sales among small retailers is traced to the different elements of the retail mix : product assortment, customer services, store atmosphere, pricing policies. store location and promotion strategies. These factors were analyzed taking onto consideration the environment. An action agenda on how to improve the productivity of small retailers was developed.
[Research Paper] : (BA 200-Business Research). -- [Iloilo City : University of the Philippines in the Visayas - College of Management], March 24, 1995.